Os estudos sobre sepulturas escavadas na rocha em Portugal, trinta anos depois - Barroca, Mário (2021)
The change of paradigm in the study of rock-cut graves, which occurred in Portugal thirty years ago, has renewed the interest in these archaeological structures. Since then, contributions have multiplied, with inventories and surveys carried out in the context of archaeological maps, academic research or simple regional studies. The amount of data accumulated in the last three decades is significant and is worth trying to synthetize the acquired knowledge. In this paper we will present a bibliographic review on the topic, particularly concerning academic works. We will also present the main aspects related to these funerary monuments, from the chronological issues, their religious affiliation and the problems related to the organization of burial spaces (in cemeteries or not).